INVENTARISASI, KARAKTERISASI MORFOLOGI, DAN UJI VIABILITAS BENIH PACAR TERE (Impatiens platypetala Lindl.) HASIL EKSPLORASI DI KAWASAN TAMAN NASIONAL BROMO TENGGER SEMERU - Elga Renjana; Apriyono Rahadiantoro; Linda Wige Ningrum; Dewi Ayu Lestari; Elok Rifqi Firdiana; Trimanto Trimanto; Shofiyatul Mas'udah; Lia Hapsari (Center for Forest Biotechnology and Tree Improvement (CFBTI), 2021)
Bromo Tengger Semeru National Park (BTSNP) is one of natural conservation areas in East Java with around 1,025 plant species. Impatiens platypetala, locally known as pacar tere, is a plant species mostly be found in mountainous areas of Java and with high potential as medicinal and ornamental plant. However, research on this species is still limited. This study was conducted to inventory, describe the morphological characteristics and test the seed viability of pacar tere in four resorts of BTSNP, namely RPTN Gunung Penanjakan, Coban Trisula, Senduro, and Ranu Darungan. Survey method was used to inventory the plant populations.Direct field observation was used to characterize the plant morphology. Seeds viability test was conducted through germination on straw paper media. The results showed that pacar tere populations were found in those four BTSNP resorts, on shade and humid habitats, also in open areas with wet soil conditions. The plant is characterized as an erect parennial herb, spursed pink flower, capsula fruit which dehiscent when ripe, with flattened cone-shaped and smooth hairy seeds. Seed germination test showed that the seeds began to germinate on day 5 after sowing (around 20 sprouts/day), epigeal type, with percentage of germination and viability was 56% and 90% respectively. Results of this study are expected to provide basic information to support the conservation efforts of I. platypetalaboth in-situ and ex-situ (seed and living plant), also its propagation efforts for further bioprospecting researches.